Wetland Bird Response to Habitat Composition and Configuration at Multiple Spatial Scales - Sica, Yanina Vanesa; Quintana, Ruben D.; Bernardos, Jaime Nicolás; Calamari, Noelia Cecilia; Gavier Pizarro, Gregorio Ignacio (Springer, 2021)
Wetlands loss has major consequences for biodiversity. The Delta of Paraná River is one of the largest wetland ecosystems in South America undergoing rapid conversion of freshwater marshes to pastures. We evaluated the response of nine wetland bird species to a gradient of landscape structure accounting for different levels of wetland loss in the Lower Delta, Argentina. We used point counts and a hierarchical distance sampling approach to assess the effects of wetland area, configuration, and land use on the density of species. Wetland area was the most important factor determining species density; most species responded positively at 100 m. The effect of wetland configuration varied among species; contiguous freshwater marsh area at 500 m only favored one species, whereas a large number of small patches of freshwater marsh benefited most species. Higher cattle density showed variable effects, and larger areas within polders reduced the density of two species. In the long term, wetland birds of the Lower Delta could decrease in density due to wetland loss and anthropogenic changes in the landscape. Our study shows the importance of considering the response of multiple species to landscape change at multiple scales and the need for a sustainable management of wetlands.